CRISPR/Cas9-deaminase enables robust base editing in Rhodobacter sphaeroides 2.4.1 - Yufeng Luo; Mei Ge; Bolun Wang; Changhong Sun; Junyi Wang; Yuyang Dong; Jianzhong Jeff Xi (Microbial Cell Factories, 2020)
Abstract Background CRISPR/Cas9 systems have been repurposed as canonical genome editing tools in a variety of species, but no application for the model strain Rhodobacter sphaeroides 2.4.1 was unveiled. Results Here we showed two kinds of programmable base editing systems, cytosine base editors (CBEs) and adenine base editors (ABEs), generated by fusing endonuclease Cas9 variant to cytosine deaminase PmCDA1 or heterodimer adenine deaminase TadA–TadA*, respectively. Using CBEs, we were able to obtain C-to-T mutation of single and double targets following the first induction step, with the efficiency of up to 97% and 43%; while the second induction step was needed in the case of triple target, with the screening rate of 47%. Using ABEs, we were only able to gain A-to-G mutation of single target after the second induction step, with the screening rate of 30%. Additionally, we performed a knockout analysis to identify the genes responsible for coenzyme Q10 biosynthesis and found that ubiF, ubiA, ubiG, and ubiX to be the most crucial ones. Conclusions Together, CBEs and ABEs serve as alternative methods for genetic manipulation in Rhodobacter sphaeroides and will shed light on the fundamental research of other bacteria that are hard to be directly edited by Cas9-sgRNA.